Inhibition of creatine kinase reduces the rate of fatigue-induced decrease in tetanic [Ca(2+)](i) in mouse skeletal muscle - Dahlstedt, Anders J (Blackwell Science Inc, 2001)
1. Ca(2+)-phosphate (P(i)) precipitation in the sarcoplasmic reticulum (SR) may cause reduced SR Ca(2+) release in skeletal muscle fatigue. To study this, we inhibited the creatine kinase (CK) reaction with 2,4-dinitro-1-fluorobenzene (DNFB). The hypothesis was that with inhibition of CK, phosphocreatine would not break down to creatine and P(i). Therefore P(i) transport into the SR would be limited and Ca(2+)-P(i) precipitation would not occur. 2. Intact single fibres from a mouse foot muscle were fatigued by repeated short tetani under control conditions or after exposure to DNFB (10 μM). The free myoplasmic concentrations of Ca(2+) ([Ca(2+)](i)) and Mg(2+) ([Mg(2+)](i)) were measured with indo-1 and mag-indo-1, respectively. Changes in [Mg(2+)](i) were assumed to reflect alterations in myoplasmic ATP concentration. 3. During the first 10 fatiguing tetani, tetanic [Ca(2+)](i) increased both in control and after DNFB exposure. Thereafter tetanic [Ca(2+)](i) fell and the rate of fall was about fourfold lower after DNFB exposure compared with control. 4. Under control conditions, there was a good relationship between declining tetanic [Ca(2+)](i) and increasing [Mg(2+)](i) during the final part of fatiguing stimulation. This correlation was lost after DNFB exposure. 5. In conclusion, the present data fit with a model where Ca(2+)-P(i) precipitation inhibits SR Ca(2+) release in fatigue produced by repeated short tetani. Furthermore, the results suggest that the rate of P(i) transport into the SR critically depends on the myoplasmic Mg(2+)/ATP concentration.